Multifunctional dendrimer-based nanoparticles for in vivo MR/CT dual-modal molecular imaging of breast cancer - Li K (Dove Medical Press, 2013)
Kangan Li,1,4,5,* Shihui Wen,2,* Andrew C Larson,4,5 Mingwu Shen,2 Zhuoli Zhang,4,5 Qian Chen,3 Xiangyang Shi,2,3 Guixiang Zhang1 1Department of Radiology, Shanghai First People’s Hospital, Shanghai Jiaotong University School of Medicine, Shanghai, People’s Republic of China; 2College of Chemistry, Chemical Engineering and Biotechnology, Donghua University, Shanghai, People’s Republic of China; 3State Key Laboratory for Modification of Chemical Fibers and Polymer Materials, Donghua University, Shanghai, People’s Republic of China; 4Departments of Radiology and Biomedical Engineering, Northwestern University, Chicago, IL, USA; 5Robert H Lurie Comprehensive Cancer Center, Chicago, IL, USA *These authors contributed equally to this work Abstract: Development of dual-mode or multi-mode imaging contrast agents is important for accurate and self-confirmatory diagnosis of cancer. We report a new multifunctional, dendrimer-based gold nanoparticle (AuNP) as a dual-modality contrast agent for magnetic resonance (MR)/computed tomography (CT) imaging of breast cancer cells in vitro and in vivo. In this study, amine-terminated generation 5 poly(amidoamine) dendrimers modified with gadolinium chelate (DOTA-NHS) and polyethylene glycol monomethyl ether were used as templates to synthesize AuNPs, followed by Gd(III) chelation and acetylation of the remaining dendrimer terminal amine groups; multifunctional dendrimer-entrapped AuNPs (Gd-Au DENPs) were formed. The formed Gd-Au DENPs were used for both in vitro and in vivo MR/CT imaging of human MCF-7 cancer cells. Both MR and CT images demonstrate that MCF-7 cells and the xenograft tumor model can be effectively imaged. The Gd-Au DENPs uptake, mainly in the cell cytoplasm, was confirmed by transmission electron microscopy. The cell cytotoxicity assay, cell morphology observation, and flow cytometry show that the developed Gd-Au DENPs have good biocompatibility in the given concentration range. Our results clearly suggest that the synthetic Gd-Au DENPs are amenable for dual-modality MR/CT imaging of breast cancer cells. Keywords: PAMAM dendrimers, gold nanoparticles, gadolinium, PEGylation, CT imaging, MR imaging, breast cancer cells